RESPONS PERTUMBUHAN TANAMAN DAN KONSENTRASI RANTAI PANJANG POLYISOPRENOID TERHADAP VARIASI NAUNGAN DAN SALINITAS PADA MANGROVE Sonneratia alba Smith. - Evan Kharogi Sinulingga; Mohammad Basyuni; Yunasfi Yunasfi (Program studi Kehutanan USU, 2015)
Mangroves has a special ability to adapt with extreme environmental conditions. This condition allows mangroves to produce secondary metabolites as chemical defenses for their sustainability. Polyisoprenoid is one of the secondary metabolites which unknown function. The purpose of this study is to analyze the growth of S. alba seedling in responsse to shade variations and salinity concentration and its influence on the concentration of long-chain polyisoprenoid. The research was conducted from August to December 2014 using Factorial Completely Randomized design with shade treatment of 0%, 25%, 50%, and 75% along with salinity levels of 0%, 1.5% and 3%. Analysis of non-saponifiable lipid content and polyisoprenoid was done by comparing the leaves and roots of S. alba seedlings in variation 0% shade and 3% with salinity variations and in 75% shade with 3% salinity. The results showed that growth of S. alba seedling was optimum variation of 0% shade and 3% salinity showing 100% growth, 2.6 cm height, 0.17 mm diameter, 0.113 g fresh weight root, 0, 08 g dry weight root, 0.15 g wet weight shoot, 0.05 g dry weight shoot, 4 leaves number and ratio shoot and roots was 0.59. Polyisoprenoid content obtained at 190,5 ml in leaves an 133,4 ml in roots from variation 0% shade and with 3% salinity but in 75% shade with 3% salinity at 185,2 ml in leaves and 231,9 ml in roots. Polyisoprenoid may play an important role in adapting the availability light intensity, which polyisoprenoid concentration increased with reducing light intensity on S. alba seedlings.Keywords : Mangroves, S. alba, shade, salinity, polyisoprenoid